2020
DOI: 10.5713/ajas.20.0360
|View full text |Cite
|
Sign up to set email alerts
|

Treated oil palm frond and its utilisation as an improved feedstuff for ruminants–An overview

Abstract: Oil palm frond (OPF) is a biomass residue from oil palm plantations that has received increasing interest for its promise as roughage resources to overcome limitations of ruminant feeding. However, the use of OPF as a feedstuff for optimal livestock productivity is limited by its high lignocellulosic content and low nutritional value. Chemical composition revealed that OPF was composed of 70% fibre and 22% soluble carbohydrates on a dry matter (DM) basis. Various physical, chemical, biological and physico-chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…OPF has a significant amount of lignin, a large complex structure present in the cell wall that has a direct impact on digestion if the quality is not improved [30]. Previous research has found that including fresh OPF in a goat's diet increases the digestibility of DM, OM, and CP by about 46.9%, 51.7%, and 41.0%, respectively [31], which is lower than ensiled OPF in this study (digestibility of more than 60%).…”
Section: Effects On Feed Intake and Apparent Total Tract Digestibilitymentioning
confidence: 99%
“…OPF has a significant amount of lignin, a large complex structure present in the cell wall that has a direct impact on digestion if the quality is not improved [30]. Previous research has found that including fresh OPF in a goat's diet increases the digestibility of DM, OM, and CP by about 46.9%, 51.7%, and 41.0%, respectively [31], which is lower than ensiled OPF in this study (digestibility of more than 60%).…”
Section: Effects On Feed Intake and Apparent Total Tract Digestibilitymentioning
confidence: 99%
“…Statically analyses in table (1) showed significances differences (P<0.01 ) in average daily gain weight and feed conversation efficiency the better T5 170 g\ lambs\day in daily gain weight than other treatment flowed T4 165 g\ lambs\day . this may be due to positive effect of local exogenous enzymes on increase growth and activity of rumen microbiome make better in digestibility and increase feed intake also showed in table 1 Compared with trade enzymes and control, this due to performances of exogenous enzymes that add to local Agriculture pollute Residue decay or bioremediation of complex bond that connected like a cement wall between cellulose and hemicellulose and another nutrient ,Increase surface area Permit rumen microorganism more attached to particles of feed, improve digestibility of feed compared with trade enzymes (21,24), The researchers prefer decay the lignin by fungi special white root fungi because have high ability to secretion wide range of lignocellosic enzymes these Tanique improve feed digestibility, increase feed intake and ruminant growth (22 ; 23). Biolysis of lignocellosic material that treated with crude extract from medium of growth white root fungi led to decrease in ADF , NDF and ADL (19) The improvement is due to active role play by enzymes that produced by white root fungi to reduce lignin content (22).…”
Section: Roughages Daily Intakementioning
confidence: 98%
“…This increases due to act of Exogenous fibro lytic enzymes (Versatile peroxidase) with have ability to destroy complex bonds between Agricultural Waste compound and made the nutrient free and improve microorganism activity in rumen ecosystem of lambs reflected to quantity Increase of feed intake (4). White root fungi have high ability to decay Cell Wall and improve nutritive value of Agricultural Waste by the enter of fungal hyphae end to cell wall and improve activity of rumen microorganism and reduce complex bonds of cell wall of low quality roughages or wood average of lignin degrade faster compare with average of degrade cellulose and hemicellulos with biological treatment with white rot fungi the treatment alteration the structure of cell wall led to increase surface area of cell wall of Agricultural Waste (12,19,20,21,22).…”
Section: Roughages Daily Intakementioning
confidence: 99%
“…Then farmers processed OPF from chopping, blending, and fermenting once a week. This procees is a method to improve OPF digestibility [14]. In the conventional model, the farmer cut and carry the grass every day to fed their cattle.…”
Section: Linking Crop and Livestock At The Farm Levelmentioning
confidence: 99%